Serratia marcescens Septic Arthritis and Osteomyelitis after COVID-19: A Case Report and Literature Review - Tantikosol, Puthi; Sumanasrethakul, Chavanont; Pakpianpairoj, Charoenchai (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Septic arthritis and osteomyelitis due to Serratia marcescens are very rare, with only a few cases reported in the literature. This report presents a case of septic arthritis and osteomyelitis of the hip joint caused by Serratia marcescens after COVID-19. Methods: A case report of a patient who had septic arthritis of Serratia marcescens was reported. A review of literature of the bone and joint infection caused by Serratia marcescens was also done. Results: The patient was successfully treated with an open arthrotomy, debridement, and intravenous antibiotics. After 9 months, the patient showed good functional outcomes, with no signs of recurrent infection. Conclusions: Septic arthritis caused by Serratia marcescens is a rare condition. Early diagnosis and urgent surgical debridement are key factors for success.